Free-fire zone / 3. - Lynch, Chris, 1962- (Vietnam, 2012)
Rudi is a newly drafted United States Marine in Vietnam, and he likes being part of a squad--but the way some of his fellow soldiers behave toward their officers, the Vietnamese, and the war itself, is starting to trouble him.